On weather signs - Theophrastus; Sider, David; Brunschön, Carl Wolfram (Leiden ; Boston : Brill, 2007)
Takes an account of various manuscripts and places the work in its historical and scientific context. This work also lays out the details of the manuscript tradition.
PREFACE; INTRODUCTION; TEXT AND TRANSLATION; COMMENTARY; APPENDIX [ARISTOTLE] ON THE LOCATIONS AND NAMES OF THE WINDS -- Victor D'Avella; BIBLIOGRAPHY; INDEX OF IMPORTANT WORDS; GENERAL INDEX; INDEX OF ANCIENT TEXTS CITED.
Includes bibliographical references (pages 227-246) and indexes.
Text in Greek with English translation on facing pages; commentary in English.
Print version record.
eBooks on EBSCOhost
Keywords: Théophraste.; Weather forecasting -- Early works to 1800.; Meteorology -- Early works to 1800.; Temps (Météorologie) -- Prévision -- Ouvrages avant 1800.; Météorologie -- Ouvrages avant 1800.; NATURE -- Weather; SCIENCE -- Earth Sciences -- Meteorology & Climatology; Meteorology; Weather forecasting; Weersverwachtingen; Early works